Where next for criminal justice? - Faulkner, David, 1934- (Policy, 2012)
The formation of a coalition government, at a time of economic crisis, is likely to prove a watershed for criminal justice. Following a review of the achievements and disappointments in criminal justice over the years, this title stimulates fresh thinking in criminal justice by considering the policies which need to be adopted.